مقارنة بين المسطحات الخضراء الطبيعية والمسطحات الصناعية في ملاعب كرة القدم في مدينة اللاذقية; الإنشاء والصيانة - دنيا, سديف (Latakia University Journal -Biological Sciences Series, 2014)
يهدف هذا البحث إلى تسليط الضوء على واقع المسطح الأخضر وسبل المحافظة على حيويته ونضارته من خلال إجراء مقارنة بين ملاعب كرة قدم بأرضية يغطيها عشب طبيعي وملاعب أرضيتها مغطاة بعشب صناعي بحسب طريقة الإنشاء والصيانة وانعكاسها على منظر المدينة الرياضية باللاذقية. أظهرت نتائج الدراسة وجود تشابه في كيفية إنشاء مسطح من العشب الطبيعي ونظيره من العشب الصناعي, فالطريقة واحدة من حيث المبدأ فيما يخص تحضير أرضية الملعب وإقامة نظام الصرف ويقتصر الاختلاف بينهما على طبقة النبت, فالعشب الطبيعي ينمو ويتطور باستمرار مكوناً بفضل نباتاته الغضة طبقة طرية بين أقدام اللاعبين وأرض الملعب فيحميهم من أضرار السقوط على الأرض ليتفوق بذلك على العشب الصناعي, كما أن العشب الصناعي لا يحتاج إلى تجهيز خلطة ترابية لزراعته, بينما يتطلب العشب الطبيعي عمليات خدمة مكثفة و هو لا يصل إلى درجة الجمال و الروعة التي نشاهدها إلا بعد جهد كبير و عناية فائقة. إن المسطحات في الملاعب التي يغطي أرضيتها عشب صناعي طريقة غير مكلفة, لا تستهلك مياه و بالتالي لا يوجد ضرورة إلى مد شبكة للري, لا تتطلب عمليات خدمة إضافية وهذا ما يفسر استخدامها في بعض الملاعب لأن صيانتها سهلة و تبقى نظيفة و بحالة جيدة و جميلة المنظر لمدة طويلة لكنها عديمة الجدوى من الناحية البيئية. كما بينت النتائج الحالة الجيدة للمسطح الأخضر الطبيعي في ستاد كرة القدم الرئيسي الذي كان وضعه أفضل مقارنة مع مسطحات الأعشاب الطبيعية في الملاعب التدريبية التي تلقى عناية أقل مما هو عليه الحال في الملعب الرئيسي. نستنتج بأن مسطحات العشب الطبيعي بحاجة إلى المزيد من عمليات الخدمة والصيانة مثل الري والقص والترقيع والتجديد وإزالة الأعشاب الغريبة ولقد تم تقديم المقترحات اللازمة. This study aims to shed light on the situation of lawn and methods to maintain its vitality and freshness through a comparison between football stadiums floor covered with natural grass and other courts floor covered with artificial turf according to the construction method, maintenance and impacts on the sport city scene in Latakia. The results showed a similarity in how to create a flat of natural grass and his counterpart from the artificial turf, The method is the same of principle with regard to the preparation of the base and set up a drainage system and limited to the difference between them on the vegetation layer, natural grasses is growing constantly to form thanks to his tender plants a soft layer between players feet and the stadium floor, so that can save them of the falling damage on the ground to overtake on the artificial turf. The artificial turf does not need to prepare a mixture for cultivation, whereas natural grass requires intensive operations service, which is not up to the degree of beauty and splendor that we see only after a great effort and great care. Lawns in the stadiums, which the floor covers with artificial grass, is not expensive method, consumes no water and then there is no interest to extend an irrigation network, does not require etcetera operations service and this interprets its use in some stadiums because the maintenance is easy and keep clean and in good condition and beautiful scenery for a long time but it is useless from an environmental perspective. The results also indicated a good case of natural lawns in the main football stadium, which was better positioned compared with natural grass surfaces in the training stadiums, that received less care than in the main stadium. We conclude that the natural grass surfaces need more maintenance and operations service such as irrigation, cutting, patching, renovation and removal of exotic herbs and has been providing the necessary suggestions.